ANALISIS KINERJA PERUSAHAAN DENGAN METODE BALANCED SCORECARD (STUDI KASUS PADA PT.PUTRA TIDAR PERKASA) - Putra, Rizki Eka (MEASUREMENT : Jurnal Program Studi Akuntansi, 2014)
This research on the analysis of the performance of the company with the method Balanced Scorecard.With their Balanced Scorecard as a performance analysis can help companies to achieve their goals effectively and in accordance with the objectives of this efficient.Hal Balanced Scorecard as a yardstick that measures not only the financial perspective will be but the measure perspective such as customer perspective, internal business process perspective, learning and growth perspective.          From these results the performance of companies with good financial perspective because it can increase significantly in 2012 despite losing the perspective great..and for general customer satisfaction for services provided by PTP and increasing new customers every tahunnya.Untuk Learning and growth perspective is said either as employees in PTP have high deficits improve will productivity.From the four perspectives PT.Putra Tidar Perkasa assessed its performance is quite good.